Gene transfer and genome editing for familial hypercholesterolemia - Canepari, Cesare; Cantore, Alessio (Frontiers in Molecular Medicine, 2023)
Familial hypercholesterolemia (FH) is an autosomal dominant inherited disease, characterized by high low-density lipoprotein (LDL) cholesterol in the circulation. High circulating LDL cholesterol in FH is due to dysfunctional LDL receptor, mainly expressed by hepatocytes. Affected patients rapidly develop atherosclerosis, potentially leading to myocardial infarction and death within the third decade of life, if left untreated. Here we introduce the disease pathogenesis and available treatment options. We highlight different possible targets of therapeutic intervention. We then review different gene therapy strategies currently under development, which may become novel therapeutic options in the future, and discuss their advantages and disadvantages. Finally, we briefly outline the potential application of some of those strategies for the more common acquired hypercholesterolemia disease.